Functionalised nitrogen heterocycles and the search for new antibacterials and bioactives - Khan, MK; Wang, D; Moloney, MG (Thieme Gruppe, 2020)
The importance of, and synthetic routes to, pyrrolidines and piperidines, along with their relevance to natural product synthesis and antibacterial drug discovery, are surveyed in the context of an extended programme of investigation from our own laboratories.